2021
DOI: 10.1177/09612033211051302
|View full text |Cite
|
Sign up to set email alerts
|

Early onset left ventricular remodeling in juvenile systemic lupus erythematosus; Insight from 3-dimensional speckle tracking echocardiography

Abstract: Background Early diagnosis and treatment of myocardial affection in patients with systemic lupus erythematosus (SLE) are crucial. Objectives To evaluate the ventricular systolic function in juvenile-onset systemic lupus erythematosus (j-SLE) patients by 3-D speckle tracking echocardiography (3D-STE) and to determine the predictors of left ventricular (LV) dysfunction if present. Methods Twenty-six SLE patients without heart failure and 21 healthy controls were studied by standard echocardiogram and 3D-STE. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…LVEF was significantly lower in almost every reported study in our meta-analysis, with very few exceptions. 20,21,[40][41][42][43][44][45][46][47][48][49][50][51][52] Left ventricular systolic function assessment with STE derived LVGLS showed consistently lower levels in every reported study without exceptions. 40,41,53,54 Interestingly, these findings are confirmed and extended by the subgroup analyses, showing similar results both in studies using 2D STE and in those using 3D STE modalities.…”
Section: Cardiovascularmentioning
confidence: 81%
See 1 more Smart Citation
“…LVEF was significantly lower in almost every reported study in our meta-analysis, with very few exceptions. 20,21,[40][41][42][43][44][45][46][47][48][49][50][51][52] Left ventricular systolic function assessment with STE derived LVGLS showed consistently lower levels in every reported study without exceptions. 40,41,53,54 Interestingly, these findings are confirmed and extended by the subgroup analyses, showing similar results both in studies using 2D STE and in those using 3D STE modalities.…”
Section: Cardiovascularmentioning
confidence: 81%
“…LVEF was significantly lower in almost every reported study in our meta-analysis, with very few exceptions. [ 20 , 21 , 40 - 52 ]…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the need for monitoring irretrievable organ damage to help provide the best care. Furthermore, most of the research in c-SLE has focused on LV functions, even on using 3DE [ 29 , 30 ]. Therefore, the current work shed light on the subclinical myocardial functional alterations of the forgotten ventricle “the RV” in asymptomatic pediatric patients with c-SLE in relation to controls using conventional ECHO, tissue Doppler, and specific emphasis on 3DE-derived parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that global longitudinal strain (GLS) is a good predictor of mortality in patients with HF, and in patients with SLE it has been shown to find significant impairment of diastolic and systolic function 5,6 and even before these changes the alterations can be detected by two-dimensional ultrasound 7 and are related to a longer duration and high SLE activity index 8 regardless of age. 9…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that global longitudinal strain (GLS) is a good predictor of mortality in patients with HF, and in patients with SLE it has been shown to find significant impairment of diastolic and systolic function 5,6 and even before these changes the alterations can be detected by two-dimensional ultrasound 7 and are related to a longer duration and high SLE activity index 8 regardless of age. 9 Diabetes mellitus (DM) is an increasingly important contributor to HF. 10 In this context, insulin resistance (IR) may play a role in the initiation and progression of metabolic cardiomyopathy affecting LV contractility and stiffness through the shift in substrate utilization toward fatty acid metabolism.…”
Section: Introductionmentioning
confidence: 99%